Нейромережева система керування електрогідроциклоном - Дудник, А.О.; Штепа, В.М.; Лисенко, В. П. (Енергетика і автоматика, 2017)
NEURAL NETWORK CONTROL SYSTEM OF ELECTROHYDROCYCLONE A. Dudnyk, V.Shtepa, V. Lysenko Annotation. The results of research of electrohydrocyclone mode, which is used for water purification are shown. Neural network control system of electrohydrocyclone as well as its hardware and software was developed. Keywords: electrotechnical complex, electrohydrocyclone, water treatment, neural network